Smoothened Is a Fully Competent Activator of the Heterotrimeric G Protein G(i) - Shen, Feng (The American Society for Pharmacology and Experimental Therapeutics, 2013)
Smoothened (Smo) is a 7-transmembrane protein essential to the activation of Gli transcription factors (Gli) by hedgehog morphogens. The structure of Smo implies interactions with heterotrimeric G proteins, but the degree to which G proteins participate in the actions of hedgehogs remains controversial. We posit that the G(i) family of G proteins provides to hedgehogs the ability to expand well beyond the bounds of Gli. In this regard, we evaluate here the efficacy of Smo as it relates to the activation of G(i), by comparing Smo with the 5-hydroxytryptamine(1A) (5-HT(1A)) receptor, a quintessential G(i)-coupled receptor. We find that with use of [(35)S]guanosine 5′-(3-O-thio)triphosphate, first, with forms of G(i) endogenous to human embryonic kidney (HEK)-293 cells made to express epitope-tagged receptors and, second, with individual forms of Gα(i) fused to the C terminus of each receptor, Smo is equivalent to the 5-HT(1A) receptor in the assay as it relates to capacity to activate G(i). This finding is true regardless of subtype of G(i) (e.g., G(i2), G(o), and G(z)) tested. We also find that Smo endogenous to HEK-293 cells, ostensibly through inhibition of adenylyl cyclase, decreases intracellular levels of cAMP. The results indicate that Smo is a receptor that can engage not only Gli but also other more immediate effectors.